2008
DOI: 10.1002/mnfr.200800010
|View full text |Cite
|
Sign up to set email alerts
|

Genistein‐ and daidzein 7‐O‐β‐D‐glucuronic acid retain the ability to inhibit copper‐mediated lipid oxidation of low density lipoprotein

Abstract: Two isoflavones in vivo metabolites, genistein-7-O-beta-D-glucuronic acid (G7G) and daidzein-7-O-beta-D-glucuronic acid (D7G) were synthesised chemically. The ability of these metabolites to scavenge an organic radical was measured by the trolox equivalent antioxidant capacity (TEAC) assay, while their reducing ability was measured by the ferric reducing antioxidant power (FRAP) assay. The TEAC and FRAP values of G7G were 45 and 51% of that of genistein, while those of D7G were 52 and 77% of that of daidzein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 60 publications
4
8
0
Order By: Relevance
“…Previous reports suggested that genistein was a substrate for several intestinal efflux transporters such as the ABCG2 gene product breast cancer resistance protein (BCRP) (Enokizono et al, 2007) and was reported to be mainly metabolized by UDP glucuronosyltransferase (UGT) to genistein glucuronide (Kgomotso et al, 2008), which can restrict systemic exposure after oral administration. G7P could be a promising alternative to genistein in increasing the contact of genistein to the epithelial membrane by improving aqueous solubility and likely by contributing to saturate intestinal efflux and metabolism, thus enhancing transepithelial flux and increasing systemic exposure (Heimbach, Fleisher, & Kaddoumi, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports suggested that genistein was a substrate for several intestinal efflux transporters such as the ABCG2 gene product breast cancer resistance protein (BCRP) (Enokizono et al, 2007) and was reported to be mainly metabolized by UDP glucuronosyltransferase (UGT) to genistein glucuronide (Kgomotso et al, 2008), which can restrict systemic exposure after oral administration. G7P could be a promising alternative to genistein in increasing the contact of genistein to the epithelial membrane by improving aqueous solubility and likely by contributing to saturate intestinal efflux and metabolism, thus enhancing transepithelial flux and increasing systemic exposure (Heimbach, Fleisher, & Kaddoumi, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Structure-activity relationship studies revealed that genistein had a 48-fold higher affinity for ER β than isoflavone daidzein because of an additional hydroxyl biophore and a 9.1-Å intramolecular distance between biophores (Larrosa, González-Sarrías, García-Conesa, Tomás-Barberán, & Espín, 2006;Morito et al, 2001). Hence, genistein is the most potent antioxidant and estrogenically active molecule among phytoestrogenic isoflavones (Kgomotso, Chiu, & Ng, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, although generally less active than the aglycone, genistein glucuronides retain the ability to prevent lipid oxidation and possess modest activity to enhance human natural killer cells at nutritionally relevant concentrations (Zhang et al, 1999b;Kgomotso et al, 2008). In addition, genistein conjugates including sulfates can serve as the reservoir of parent compound in vivo by being substrates for futile (both enteric and enterohepatic) recycling and for hydrolysis in tissues (Sfakianos et al, 1997;Chen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, Kapiotis et al [87] have reported that only genistein (2.5 μM), not daidzein, inhibits in vitro LDL oxidation. Interestingly, equol and 8-hydroxydaidzein, principal metabolites of daidzein, are potent inhibitors of oxLDL generation than the parent daidzein [89,90]. These in vitro studies have also been supported by in vivo animal studies.…”
Section: Soy and Foam Cell Formationmentioning
confidence: 86%